2017
DOI: 10.1371/journal.pone.0169300
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H2-Blocker and Proton Pump Inhibitor Use and the Risk of Pneumonia in Acute Stroke: A Retrospective Analysis on Susceptible Patients

Abstract: BackgroundAlthough histamine H2-blockers (H2B) and proton pump inhibitors (PPI) are used commonly to prevent gastrointestinal bleeding in acute stroke, they are implicated in the increased risk of pneumonia in other disease populations. In acute stroke, the presence of distinctive risk factors of pneumonia, including dysphagia and impaired consciousness, makes inclusive analysis vulnerable to confounding. Our aim was to assess whether acid-suppressive drugs increase pneumonia in acute stroke in a population co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
1
29
0
2
Order By: Relevance
“…Kalra et al [31] and Kalra et al [32] used the same RCT data. Study designs included RCTs (30%) [15,[31][32][33], prospective (20%) [13,34] and retrospective (40%) [35][36][37][38] observational studies and one quasi-experimental design [39]. Europe hosted 55% of studies [15,[31][32][33][34]37], Australia 27% [13,36,38] and Japan 18% [35,39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kalra et al [31] and Kalra et al [32] used the same RCT data. Study designs included RCTs (30%) [15,[31][32][33], prospective (20%) [13,34] and retrospective (40%) [35][36][37][38] observational studies and one quasi-experimental design [39]. Europe hosted 55% of studies [15,[31][32][33][34]37], Australia 27% [13,36,38] and Japan 18% [35,39].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported pneumonia during hospitalization [33,34,37,39]. Three studies reported within 14 days of admission [31,32,35] and one from 7 days of admission [36]. Warusevitaine et al [15] and Langdon et al [13] reported at 21 days and 30 days, respectively.…”
Section: Diagnosis and Frequency Of Sapmentioning
confidence: 99%
See 1 more Smart Citation
“…GERD is considered to be a risk factor for COPD exacerbations and this can further increase the mortality in this group of patients (73). The use of acid suppressing agents (histamine-2 receptor antagonists and proton pump inhibitors) which are commonly used in GERD are associated with an increased risk of stroke-associated pneumonia (SAP) (74,75). The compromised immune state and the use of corticosteroids already puts COPD patients at higher risk for pneumonia (76).…”
Section: Impact Of Stroke On Copd Outcomesmentioning
confidence: 99%
“…There is emerging evidence for the use of preventative measures such as screening for stroke-induced immunosuppression and dysphagia, for identifying patients at high risk for SAP [15]. Further studies are needed to test this and screening for oral aerobic Gram-negative bacteria [16] as well as the need to evaluate if treatment with proton pump inhibitors [17] and nasogastric tubes (NGT) [18][19][20] are associated with SAP in patients with dysphagia.…”
Section: Introductionmentioning
confidence: 99%